Four-dimensional Multiphase Steady-State MRI with Ferumoxytol Enhancement: Early Multicenter Feasibility in Pediatric Congenital Heart Disease - Nguyen, Kim-Lien (Radiology, 2021)
BACKGROUND: The value of MRI in pediatric congenital heart disease (CHD) is well recognized; however, the requirement for expert oversight impedes its widespread use. Four-dimensional (4D) multiphase steady-state imaging with contrast enhancement (MUSIC) is a cardiovascular MRI technique that uses ferumoxytol and captures all anatomic features dynamically. PURPOSE: To evaluate multicenter feasibility of 4D MUSIC MRI in pediatric CHD. MATERIALS AND METHODS: In this prospective study, participants with CHD underwent 4D MUSIC MRI at 3.0 T or 1.5 T between 2014 and 2020. From a pool of 460 total studies, an equal number of MRI studies from three sites (n = 60) was chosen for detailed analysis. With use of a five-point scale, the feasibility of 4D MUSIC was scored on the basis of artifacts, image quality, and diagnostic confidence for intracardiac and vascular connections (n = 780). Respiratory motion suppression was assessed by using the signal intensity profile. Bias between 4D MUSIC and two-dimensional (2D) cine imaging was evaluated by using Bland-Altman analysis; 4D MUSIC examination duration was compared with that of the local standard for CHD. RESULTS: A total of 206 participants with CHD underwent MRI at 3.0 T, and 254 participants underwent MRI at 1.5 T. Of the 60 MRI examinations chosen for analysis (20 per site; median participant age, 14.4 months [interquartile range, 2.3–49 months]; 33 female participants), 56 (93%) had good or excellent image quality scores across a spectrum of disease complexity (mean score ± standard deviation: 4.3 ± 0.6 for site 1, 4.9 ± 0.3 for site 2, and 4.6 ± 0.7 for site 3; P < .001). Artifact scores were inversely related to image quality (r = –0.88, P < .001) and respiratory motion suppression (P < .001, r = –0.45). Diagnostic confidence was high or definite in 730 of 780 (94%) intracardiac and vascular connections. The correlation between 4D MUSIC and 2D cine ventricular volumes and ejection fraction was high (range of r = 0.72–0.85; P < .001 for all). Compared with local standard MRI, 4D MUSIC reduced the image acquisition time (44 minutes ± 20 vs 12 minutes ± 3, respectively; P < .001). CONCLUSION: Four-dimensional multiphase steady-state imaging with contrast enhancement MRI in pediatric congenital heart disease was feasible in a multicenter setting, shortened the examination time, and simplified the acquisition protocol, independently of disease complexity. Clinical trial registration no. NCT02752191 © RSNA, 2021 Online supplemental material is available for this article. See also the editorial by Roest and Lamb in this issue.